Seas of life - Honeyborne, James; BBC Learning (Australia: BBC Learning, 2005)
This series visits the cricual moments in life's journey to dominate the earth.' Seas of life' reveals that the basic blueprint of brain, backbone, 2 legs and 2 arms was created in the ocean.
Photography, Simon wagen ; executive producer, Michael Gunton ; series producer, Miles Barton
Keywords: Ocean; Marine biology